The effect of leftward bias on visual attention for driving tasks. (April 2020) - Zheng, Xinyi; Yang, Yanqun; Easa, Said; Lin, Wei; Cherchi, Elisabetta
Highlights: New evidence on the pseudoneglect and its impact on driving safety. Differences in the visual scan patterns between experience and inexperienced drivers. New evidence from lab experiments using simulator and eye-tracker. Experienced drivers have more skilled visual scan pattern than inexperienced drivers. Inexperienced drivers can improve space-scanning ability via eye movement training. Abstract: The leftward bias of driving visual attention has been found to explain the role of driving experience in the visual attention strategy; even though the results reported in the literature are not always consistent. This study aims to explore the driving attention characteristics and the eye movement patterns by using a simulated driving experiment in conjunction with an eye-tracker device. 31 young inexperienced drivers (undergraduate students, average age 21) and 30 old experienced drivers (taxi drivers, average age 36) took part in the experiment. Results show that the eye movement patterns of the drivers have certain similarity in the occurrence of subtle asymmetries of visual attention favouring left space (the direction of the driving in the experiment was right-side) and that they are related to the right hemisphere specialization for spatial attention. However, in the more experienced drivers the leftward eye movement tends to shift toward the centre or even rightward to pay attention to the hazard events on road. These results suggest that inexperienced drivers are initially aroused by natural biological leftward visual attention and likely to develop central and rightward eye movement strategy for safety diving purpose. The implications of this study suggest that, despite the existence of natural visual attention bias, the left asymmetries in visual scan in inexperienced drivers still can be modified by driving trainings that focus on the hazard situation on road.